The optimisation of a preselection methodology of heterotypic spheroids for the in vitro investigation of angiogenesis in lung cancer. - De Agrela Gomes, Daniella Anthea (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2025)
Lung cancer, particularly non-small cell lung cancer (NSCLC), is a leading cause of cancer-related deaths. Angiogenesis, the formation of new blood vessels, is essential for disease progression. The tumour microenvironment significantly influences angiogenesis in NSCLC. Despite challenges in accurately modelling lung anatomy, current in vitro 3D cell models can provide insights into NSCLC interactions and potential therapeutic targets. 3D cell model advancements such as heterotypic spheroids have led to more relevant models for tumour growth mechanism study. However, determining if spheroids are well-formed for consistent use in subsequent experiments or complex cell models such as lung-on-a-chip needs to be addressed. This study is aimed to develop a 3D spheroid model made of multiple cell lines as tools for investigating the angiogenic switch, which is known to trigger the rapid growth of malignant cells in association with new blood vessel formation. Tumour spheroids, self-assembling structures composed of multiple cells, can replicate key tumour features compared to 2D cultures. The hypothesis behind the proposed multicellular 3D spheroids for the lung is that the spheroids can facilitate early expression of angiogenic markers in complex models and was evaluated by assessing spheroid morphology, viability, proliferation, hypoxia, and angiogenic marker expression. Viability assessment of homotypic and heterotypic spheroids showed stable ATP production, indicating sustained cell viability. Preselecting spheroids based on size and morphology, such as circularity and solidity, minimises variability in experimental outcomes. This study highlights that larger spheroids (≥ 400 μm) with uniform morphology are critical for replicating hypoxic conditions in NSCLC models. Co-culturing A549 spheroids with MRC-5 fibroblasts enhances ECM formation and spheroid aggregation, improving the physiological relevance of these 3D models. Immunofluorescence staining and western blot analysis preliminary confirmed increased HIF-1α expression. It demonstrates spheroid size correlates with hypoxia and supports the use of this model for studying tumour microenvironments. In conclusion, my work demonstrates that by precisely controlling the cell seeding parameters (cell types, densities and ratios), it is possible to fabricate highly reproducible tumour spheroid models that mimic key aspects of the tumour.
APPROVED
Keywords: Microscopy; Circularity; angiogenesis; NSCLC; Spheroids